STRATEGI HEDGING TIONGKOK MERESPON STRATEGI INDO-PASIFIK AMERIKA SERIKAT TAHUN 2016-2024 - Fitra, Rakha Athaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The rivalry between China and the United States has become a fixture of international politics in the 21st century. China's ambition to become a new superpower clashed with the United States' interest in maintaining its status as the hegemon in the Indo-Pacific region. To that end, the United States formulated the Indo-Pacific strategy, with one of the goal is to contain China's influence in the region. In response, China has adopted a hedging strategy in order to respond to the United States strategy. The research uses qualitative research approach, with data collection techniques using literature study techniques sourced from several journal articles, books, documents, and official websites. This research uses hedging theory to help explain China’s behavior when responding to the Indo-Pacific Strategy of the United States. The results showed that the Chinese government has shown various policies that could be categorized as hedging behavior when responding to the United States’ Indo-Pacific Strategy, through strategies such as indirect balancing, economic diversification, and limited bandwagoning. Through hedging, China can adopt a more flexible policies when interacting with the United States. Keywords: Indo-Pacific, China, United States, Hedging